Asthma Action Plans and Patient Satisfaction Among Women With Asthma - Patel, Minal R. (American College of Chest Physicians, 2012)
BACKGROUND: Asthma action plans (AAPs) are a priority recommendation of the National Asthma Education and Prevention Program and have been shown to positively affect health outcomes. Patient satisfaction is an important clinical outcome, yet little is known about its association with receiving an AAP. This study examined the association between having an AAP and behaviors to keep asthma in control and patient satisfaction with care. METHODS: The study design was a cross-sectional analysis of baseline data from a randomized trial evaluating a self-management program among 808 women with asthma. Participants reported demographic information, interactions with clinicians, whether they had an AAP and owned a peak flow meter, self-management behaviors, and symptoms. RESULTS: The mean age of the participants was 48 ± 13.6 years, 84% (n = 670) were satisfied with their asthma care, and 48% (n = 383) had a written AAP from their physician. Women not having an AAP were less likely to take asthma medication as prescribed [χ(2)(1) = 13.68, P < .001], to initiate a discussion about asthma with their physicians [χ(2)(1) = 26.35, P < .001], and to own a peak flow meter [χ(2)(1) = 77.84, P < .001]. Adjusting for asthma control, income, and medical specialty, women who did not have an AAP were more likely to report dissatisfaction with their asthma care (OR, 2.07; 95% CI, 1.35-3.17; P < .001). CONCLUSIONS: Women without an AAP were less likely to initiate discussions with their physicians, take medications as prescribed, and own a peak flow meter to monitor asthma, all considered important self-management behaviors. They were also less satisfied with their care. Not having an AAP may affect interactions between patient and physician and clinical outcomes.